PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA TENAGA MEDIS DAN NON MEDIS (Studi Pada Puskesmas Kecamatan Brang Ene) - Vivin Fitryani; Ira Febrianty; Wahyu Haryadi (Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the effect of financial compensation on the performance of medical and non-medical personnel at the Brang Ene District Health Center, West Sumbawa Regency. This research is an associative study to examine the effect of financial compensation on the performance of medical and non-medical personnel at the Brang Ene District Health Center, West Sumbawa Regency. The type of data used is quantitative data in the form of respondents' responses in answering the questions given which were obtained directly from the research subject through a questionnaire. The population in this study were all medical and non-medical personnel at the Brang Ene District Health Center, West Sumbawa Regency, totaling 53 people and the entire population would be taken as the research sample. The data that has been collected is processed using the SPSS program to be studied using simple linear regression analysis techniques, individual hypothesis testing (t test), and determining coefficient test (R2). The results of this study indicate that financial compensation has a positive and significant effect on the performance of medical and non-medical personnel at the Brang Ene District Health Center, West Sumbawa Regency. the ability of the financial compensation variable to influence variations in the performance variables of medical and non-medical personnel at the Brang Ene District Health Center, West Sumbawa Regency, was 57.9%, while the remaining 42.1% was influenced by other variables outside the scope of this study.